Laparoscopic combined portal vein ligation and venous outflow deprivation for staged hepatectomy with insufficient future liver remnant volume: A technical note with video vignette - Tao Liu; Wenjiu Song; Jianhua Huang; Xinyu You; Jianjie Hao; Donghui cheng; Yu Zhang (Asian Journal of Surgery, 2025)
Technique: Previous techniques for augmenting Future Liver Remnant (FLR) volume primarily include Portal Vein Embolization (PVE), Liver Venous Deprivation (LVD), and Associating Liver Partition and Portal vein Ligation for Staged hepatectomy (ALPPS). Furthermore, previous techniques were characterized by insufficient liver hypertrophy capacity, as well as higher difficulty and risk. We have developed a new technique through laparoscopic surgery, which involves Combined Portal Vein Ligation and Outflow Deprivation (CPLOD), by ligating the portal vein and dissecting the hepatic vein and short hepatic veins on the affected side. The present study reported the surgical details and accompanied with the video. Results: The CPLOD achieved a 100 % technical success. In the first-stage surgery, 1 of 11 patients had CPLOD with left hepatic lesion resection; the others had CPLOD only. Pre- CPLOD, median FLR was 381.7ml (310.5–419.7ml) and FLR/TLV was 26.4 % (24.1%–33.7 %). At 28 days post- CPLOD, FLR increased to 639.4ml (578.3–805.5ml) with FLR/TLV at 45.9 % (42.1%–59.2 %). Kinetic growth rate was 4.54 ± 1.36 weekly, with a 75.96 ± 19.77 % relative increase. No major complications occurred, and all underwent R0 resection in the second-stage surgery without liver failure or mortality. Conclusions: Study results affirm CPLOD as a safe and efficacious technique for selected cases, notable for rapid FLR growth, marking it as a promising surgical innovation.